2017
DOI: 10.3126/medphoenix.v2i1.18384
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Mothers Regarding Home Care of Children undergone Cardiac Surgery with a View to Develop an Information Booklet

Abstract: Background: Children in developing countries are now receiving surgical repair for congenital heart defects. Despite advancement in the medical and surgical field, in developing countries where we have severe budgetary constraints, lack of funding for maintenance, poverty, skilled manpower deficit and knowledge deficit among public, pediatric cardiac surgery still remains a major challenge. For the parents of those children undergone corrective surgery more in-depth educational sessions are required to enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This result supported by Chuambangphae et al [20] Limited studies discussed mothers' experience of knowledge and skills regarding home care of their children with open heart surgery. Meanwhile, the study conducted by Poudel et al [21] revealed mothers' skills deficit regarding care of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result supported by Chuambangphae et al [20] Limited studies discussed mothers' experience of knowledge and skills regarding home care of their children with open heart surgery. Meanwhile, the study conducted by Poudel et al [21] revealed mothers' skills deficit regarding care of their children.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed a highly significant correlation between mothers' knowledge and their age, and level of education, this result was agreed with. [21] The researcher's point of view suggests that, the mothers' needs to gain knowledge and practice regarding discharge care of their children after heart surgery. The educational session was effective in improving mothers' knowledge and reported practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the rst home follow-up, the most common problems noted among the mothers in the intervention group were de cient knowledge, di culty in a caregiver role, and ineffective health/treatment management. The literature includes studies reporting the maternal problems such as the lack of knowledge regarding home care after surgery [29], ineffective coping and di culties in providing care to the infants, and attritubes these problems to the need for support during home care [11,16]. It was identi ed that insu cient knowledge and skills as the leading factors contributing to postdischarge stress in mothers [8].Constant evaluation of the level of information, health training, and counseling for infant care during home follow-ups are the nursing interventions that help to eliminate the lack of knowledge.…”
Section: Nursing Diagnosesmentioning
confidence: 99%